The Motivational Framing of Self-Love in Kim Namjoon’s UNICEF Speech - Sulfani, Fifi; Nuriadi; Baharuddin (Journal of Authentic Research, 2026)
This study aims to analyze the representation of self-love as a motivational message in Kim Namjoon’s (RM) speech at the United Nations General Assembly in 2018. Using qualitative Discourse Analysis method, this research examines how self-love is constructed linguistically and rhetorically through Discourse Representation Theory (Kamp & Reyle, 1993) and Self-Compassion Theory (Neff, 2003). The primary data consist of the official transcript of RM’s UNICEF speech, which was analyzed by identifying and categorizing utterances related to self-love. The findings reveal that self-love is represented through three main dimensions: personal identity, collective identity, and motivational elements. Linguistic strategies such as pronoun use, lexical choice, and repetition, as well as rhetorical devices including metaphor, direct address, and narrative technique, play a significant role in strengthening the message. The analysis shows that RM constructs self-love as a reflective, shared, and action-oriented process, encouraging audiences particularly adolescents and young people to accept themselves, recognize common human struggles, and confidently express their identities. This study contributes to discourse analysis by highlighting how motivational messages are shaped through language and offers insight into the role of public speeches in promoting psychological well-being among youth.